2020
DOI: 10.1155/2020/8050186
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Resident Type 2 Innate Lymphoid Cells Arrest Alveolarization in Bronchopulmonary Dysplasia

Abstract: Bronchopulmonary dysplasia (BPD) is a severe complication of the respiratory system associated with preterm birth. Type 2 innate lymphoid cells (ILC2s) play a major role in tissue homeostasis, inflammation, and wound healing. However, the role in BPD remains unclear. The present study showed that ILC2s, interleukin-4 (IL-4), IL-13, and anti-inflammatory (M2) macrophages increased significantly in BPD mice as compared to the control mice. Administration with recombinant mouse IL-33 amplified the above phenomena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Consistent with previous research, 4 , 9 , 10 this study found that AMs expression increased in BPD mice. Depletion of macrophage partially abolished the EMT process of AECII and alleviated pulmonary differentiation arrest, further supporting that macrophages are regulators of arrested alveolarization in BPD.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with previous research, 4 , 9 , 10 this study found that AMs expression increased in BPD mice. Depletion of macrophage partially abolished the EMT process of AECII and alleviated pulmonary differentiation arrest, further supporting that macrophages are regulators of arrested alveolarization in BPD.…”
Section: Discussionsupporting
confidence: 93%
“… 3 Previously, we provided evidence that AMs were elevated in the lungs of BPD mice. 4 We hypothesized that AM polarization plays a vital role in the repair of alveolar structure and lung abnormalities in BPD. Furthermore, recent studies have suggested that AM activation is associated with IL‐33 levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, ILC2s are amateur antigen-presenting cells (APC) that can cooperate with dendritic cells (DCs) to maintain type 2 immune response [ 48 ]. ILC2s not only mediate neonatal lung development [ 49 ], but also play a role in lung diseases caused by developmental abnormalities, such as bronchopulmonary dysplasia [ 50 ]. The phenotypes of ILC2s in different models of airway inflammation are different, as manifested by ILC2s-specific expressed genes stimulated by house dust mites.…”
Section: Ilc2s In Lung Homeostasismentioning
confidence: 99%
“…These findings, along with those by Saluzzo et al that determined that IL-33 is not required for alveolarization (32), suggest a possible role for Areg+/Icos+ tissue-repairing ILC2 in the lung developmental process. Furthermore, a recent mouse study indicated that bronchopulmonary dysplasia (BPD), a severe complication of the respiratory system seen in preterm infants, was induced by IL-33/ILC2 signaling caused by an arrest in the process of alveolarization, determining a major destructive role of tissue-resident IL-13+ILC2 in the lung (36). This differentiation could help to identify mechanisms for divergent responses caused by alterations in ILC2 during early-life.…”
Section: Ilc2 In the Developing Lungmentioning
confidence: 99%